Numerical Methods for Advection Problem (European Journal of Pure and Applied Mathematics, 2020)
This work is part of mathematical modeling and numerical analysis. This paper aims is to solve an advection problem where u=u(x; t) is the solution by Lax-Wendrof and nite dierence methods, to study the analytical stability in L2[0;1], L1[0; 1], then calculate the truncation error of these methods and nally study the analytical convergence of these methods. These numerical techniques of resolution were implemented in Scilab.